Exploring Condition-Specific Variability in the Ureteral Stent Microbiome - Ava Mousavi; Karan N. Thaker; James E. Ackerman; Niccole Diaz; Rick Martin; Craig D. Tipton; Nick Tallman; Lina Marcella Henao; Nima Nassiri; Jeffrey Veale; Anne Lenore Ackerman; Kymora B. Scotland (Pathogens)
(1) Background: Indwelling ureteral stents are commonly used urological devices to maintain ureteral patency, yet they have been associated with complications such as infections. Some studies have shown that bacteria adhere to and create an antimicrobial-resistant biofilm on stents. One factor that may impact biofilm formation is the original condition informing stent placement, such as kidney stones and renal allografts. Both kidney stones and renal allografts are independently associated with infection, yet the differential stent microbiomes of these populations remain poorly characterized. Our objective was to characterize these microbiomes in order to inform urological health practice and help prevent ureteral stent-associated infections. (2) Methods: Stents were collected from kidney stone and renal transplant recipients undergoing routine cystoscopic stent removal. Microbial DNA was extracted from stents and analyzed using 16S Next Generation Sequencing. Descriptive statistics, alpha diversity, and beta diversity methods were used for statistical analysis. (3) Results: The microbiome of ureteral stents in kidney stone and transplant patients is composed of unique species, each with different biofilm-forming abilities. (4) Conclusions: Our findings demonstrate that the microbiome of stents differs based on preceding condition. It is important to conduct future studies that explore this microbiome further to understand what type of stent-associated infection someone may develop based on their initial condition.